The rise of the Team Europe approach in EU development cooperation: Assessing a moving target - Niels Keijzer; Aline Burni; Benedikt Erforth; Ina Friesen (Deutsches Institut für Entwicklungspolitik (DIE), 2021)
This paper analyses the European Union's (EU) evolving motivations, priorities and current approaches to development cooperation under the label of 'Team Europe', following its introduction in April 2020 as the European Union's global response to the COVID-19 pandemic. It assesses what Team Europe is, to what extent and how the Team Europe approach has changed the EU's development cooperation, which effects it has on EU initiatives to support partner countries, and discusses the implications of Team Europe on the EU's development policy in the medium and long term. The paper analyses the Team Europe approach along four dimensions, which are traditionally emphasised in the EU's development policy: (i) visibility, (ii) effectiveness, (iii) ownership and (iv) integration. It concludes that Team Europe primarily seeks to increase the visibility of EU's actions in support of partner countries and prioritises European ownership of cooperation priorities over developing country ownership. Although 'effectiveness' efforts focus on improving efficacy of the intra-EU-MS coordinated processes, it remains unclear whether Team Europe promotes more programmatic collective action among member states.
Keywords: 330